Immunotherapy for EGFR-mutant advanced non-small-cell lung cancer: Current status, possible mechanisms and application prospects - Shi, Chunyan; Wang, Yan; Xue, Jianxin; Zhou, Xiaojuan (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors (ICIs) are effective against advanced and even perioperative non-small-cell lung cancer (NSCLC) and result in durable clinical benefit, regardless of programmed death ligand-1 (PD-L1) expression status in cancer. Existing clinical evidence shows that the effect of immunotherapy in patients with EGFR-mutant NSCLC after the development of tyrosine kinase inhibitor (TKI) resistance is not satisfactory. However, compared with monotherapy, ICIs combined with chemotherapy can improve the efficacy. Encouragingly, compared with that of patients with sensitive mutations, the progression-free survival of patients with rare mutations who were treated with ICIs was increased. Adequately maximizing the efficacy of ICIs in EGFR-mutant NSCLC patients is worth exploring. In this review, we described preclinical and clinical studies of ICIs or combined therapy for EGFR-mutant NSCLC. We further focused on EGFR mutations and the cancer immune response, with particular attention given to the role of EGFR activation in the cancer-immunity cycle. The mechanisms for the natural resistance to ICIs were explored to identify corresponding countermeasures that made more EGFR-mutant NSCLC patients benefit from ICIs.